Correlates of sedentary behavior in middle-aged and old age people with mild cognitive impairment: a multinational study. (16th October 2018) - Vancampfort, Davy; Stubbs, Brendon; Lara, Elvira; Vandenbulcke, Mathieu; Swinnen, Nathalie; Koyanagi, Ai
ABSTRACT: Objective: Despite the benefits of being active for people with mild cognitive impairment (MCI) on cognition and the acknowledgement that MCI is a critical period for intervening to prevent dementia, little is known about the actual sedentary levels in people with MCI. This study investigates correlates of sedentary behavior (SB) in people with MCI. Design: This was a cross-sectional study. Setting: Data from the World Health Organization's Study on Global Ageing and Adult Health were analyzed. Participants: Individuals aged ≥50 years with MCI were included. Measurements: SB was assessed by the Global Physical Activity Questionnaire. Associations between SB levels and the correlates were examined using multivariable linear and logistic regressions. Results: 4, 082 individuals aged ≥50 years with MCI (64.4 ± 17.0 years; 55.1% female) were included. The prevalence of high SB (i.e., ≥8 hours/day) was 14.0% (95%CI = 12.2%–16.0%), while the time spent sedentary was 262 ± 290 minutes/day. Correlates significantly associated with being sedentary ≥8 hours/day and time spent sedentary per day were, older age, being unemployed, depression, sleep problems, obesity (vs. normal weight), diabetes, stroke, poor self-rated health, and lower levels of social cohesion. Conclusions: Future research exploring interventions to reduce SB in people with MCI should target the identified sociodemographic and mental and physical health correlates, while the promotion of social cohesion may have the potential to increase the efficacy of future public health initiatives.